The Impact of Climate Change on Jute Production in Gaibandha District, Bangladesh - Ibrahim Hossain; Rima Akter Rakhi; Shahorare Ahomed; Mst. Shifat Rumana; Abdullah-Al-Mamun; Md. Mostafizur Rahman (International Journal of Climate Conditions, 2025)
Jute plays a crucial role in Bangladesh’s agricultural economy, especially in Gaibandha District, where it is a key crop for rural livelihoods. However, climate change, characterized by rising temperatures and unpredictable rainfall, poses significant threats to jute production. While numerous studies have explored the broader impact of climate change on agriculture, there is a gap in understanding how localized climate conditions specifically affect jute farming in Gaibandha, with many existing studies generalizing across the country and overlooking the district’s unique challenges.This study examines the impact of climate change on jute production in Gaibandha, using a mixed-methods approach that combines quantitative climate data (2014–2023) and agricultural statistics with qualitative insights from 50 farmer interviews. The results show a steady increase in average temperatures, often exceeding 36°C, disrupting photosynthesis and causing water stress, which affects plant growth and yields. Declining rainfall during the key growing months of May to August further hinders germination and retting, resulting in poor fiber quality. A multiple linear regression analysis indicated that temperature alone explained 70% of yield variability (R² = 0.7), but additional variables like rainfall and soil conditions are needed for a more accurate model.The study also identified significant socio-economic barriers, such as limited access to climate-smart resources and inadequate institutional support, which exacerbate the challenges farmers face. This research provides unique insights into Gaibandha’s vulnerabilities, emphasizing the need for targeted adaptation strategies like drought-resistant jute varieties, modern retting technologies, and better institutional support. Future research should expand to other regions, include more variables, and assess the effectiveness of climate adaptation policies.
Keywords: Agriculture; Climate change; Gaibandha District; Jute Production; adaptation strategies